Políticas Públicas e Segurança Social: Da Proteção à (Des)Coesão Social - Caeiro, Joaquim Croca (2020)
This article aims at analysing social welfare as a state instrument guaranteeing the satisfaction of the collective needs of citizens, especially those resulting from their social dimension and the repercussions it can have on the promotion of social cohesion in Portugal. The social cohesion is extended as a dialectic between instituted mechanisms of social inclusion and exclusion and the responses, perceptions and citizens’ dispositions regarding the ways these mechanisms work. Social cohesion is thus associated to an even access to economic processes results through corrective policies of unequal income distribution and a commitment to quality of life standards. It argues that social cohesion is not attainable through the use of the privileged element for the effect: the Social Welfare mechanisms provided by the state. They are not able, on their own, to guarantee the set of responses needed, namely, reducing inequalities, eliminating poverty and increasing citizen participation in society.